'As if eavesdropping on actual filming': The origins of the wildlife making-of documentary genre. Issue 2 (1st September 2018) - Gouyon, Jean-Baptiste
The wildlife making-of documentary (MOD) genre has become a routine appendage to most prestige natural history series. However, the genre is a fairly recent one. The first attempt at producing a wildlife MOD was the half-hour long Unarmed Hunter in 1963. The first wildlife MOD accompanying a natural history programme was 1984's The Making of the Living Planet. In between these two films, the televising of natural history became a profession revolving around the technical mastery of the filmmaking apparatus. Looking at the genesis of the wildlife MOD genre from the early 1960s to the early 1980s, this article examines how natural history broadcasters enroled science and scientists in their effort to carve a cultural space for the televising of natural history out of the one occupied by amateur natural history. In so doing, they promoted a definition of filmmaking as a means to produce original knowledge of the natural world.